Influence of School Physical Facilities on Students' Discipline in Public Secondary Schools in Makueni County, Kenya - Maingi, Dominic; Mulwa, David; Maithya, Redempta; Migosi, Joash (American Journal of Education and Learning, 2017)
Students' discipline is critical to the attainment of positive school outcomes. However, learning institutions have been plagued with cases of students’ unrest which undermine quality education. This study sought to investigate the influence of school physical facilities on students’ discipline in public secondary schools in Makueni County, Kenya. The objectives of the study were: to determine the influence of adequacy of classrooms on students' discipline, to establish the influence of school library facilities on students’ discipline, to establish the influence of science facilities on students' discipline and to determine the influence of adequacy of sports grounds on students' discipline. Descriptive survey design was employed. The target population was 324 principals, 3,865 teachers and 97,200 students in public secondary schools in Makueni County. The sample size of the study was obtained by stratified and simple random sampling procedures. The total sample matrix was 68 principals, 350 teachers and 380 students. Questionnaires, interview guide and observation schedule research instruments were utilized for the study. Test-retest technique of reliability was used to affirm the reliability of the instruments. The reliability coefficient of the instruments was 0.765 for questionnaire for students and 0.814 for questionnaire for the teachers. Data was analyzed using descriptive and inferential statistics and presented in frequency tables. Pearson Product Moment Correlation Coefficient was used to test the hypothesis. From the data analysis, it was found out that adequacy of physical facilities had significant positive relationship at r=+0.78, P=0.002 with levels of students' discipline in public secondary schools in Makueni County. The study recommended that educational stakeholders should expand school physical facilities in order to enhance students’ discipline.